Profile of crosstalk between glucose and lipid metabolic disturbance and diabetic cardiomyopathy: Inflammation and oxidative stress - Chen, Meng-Yuan; Meng, Xiang-Fei; Han, Yu-Peng; Yan, Jia-Lin; Xiao, Chi; Qian, Ling-Bo (Frontiers in Endocrinology, 2022)
In recent years, the risk, such as hypertension, obesity and diabetes mellitus, of cardiovascular diseases has been increasing explosively with the development of living conditions and the expansion of social psychological pressure. The disturbance of glucose and lipid metabolism contributes to both collapse of myocardial structure and cardiac dysfunction, which ultimately leads to diabetic cardiomyopathy. The pathogenesis of DCM is multifactorial, including inflammatory cascade activation, oxidative/nitrative stress, and the following impaired Ca2+ handling induced by insulin resistance/hyperinsulinemia, hyperglycemia, hyperlipidemia in diabetes. Some key alterations of cellular signaling network, such as translocation of CD36 to sarcolemma, activation of NLRP3 inflammasome, up-regulation of AGEs/RAGE system, and disequilibrium of micro-RNA, mediate diabetic oxidative stress/inflammation related myocardial remodeling and3nd lipid metabolic disturbance. Here, we summarized the detailed oxidative stress/inflammation network by which the abnormality of glucose and lipid metabolism facilitates DCM as well as the potential therapeutic regimen.